Susceptibility to Babesiosis, an Infectious Disease of Erythrocytes. - Wilson, Carrie Haas. (Tufts Archival Research Center, 2005)
Babesiosis is an emerging infectious disease caused by the intraerythrocytic parasite Babesia microti. Young, healthy individuals usually experience asymptomatic infection or mild illness, whereas elderly or immunocompromised individuals are at risk for severe disease. In these cases, symptoms and parasitemia may persist for several months. The genetic and immunologic determinants of resistance to B. microti infection are poorly understood. Using the susceptible DBA/2 (D2) strain and the resistant C57Bl/6 (B6) strain, the laboratory mapped the main determinant of resistance in young mice to an interval in the mid/proximal region of chromosome 9. I infected B6.D2 strains that vary by the lengths of their congenic intervals, and narrowed the main determinant to a list of 14 genes. The laboratory had observed that lack of the cd4 gene renders B6 mice susceptible to babesiosis, but that parasitemia eventually resolves. In depletion experiments, I confirmed that B cells are required for resolution of parasitemia in cd4-/- B6 mice, but not in wild type B6 mice. I developed a flow cytometry based assay to quantify IgG subisotypes in plasma samples from B. microti infected mice. I observed that IgG1 and IgG3 are specific of B. microti whereas IgG2b and IgG2c also recognize moieties of erythrocytes. I established that the antibody response is delayed, but concomitant to resolution of parasitemia in cd4-/- mice. I established that B cells are critical for resolution of parasitemia in young, but less so in aged DBA/2 mice. These studies have yielded insights on host resistance/susceptibility to babesiosis.; At the request of the author, this graduate work is not available to view in the Tufts Digital Library until August 15, 2018.